Georg Simmel et la mode berlinoise autour de 1900 - Philipp Jonke (Recherches Germaniques)
Georg Simmel’s fashion theory is a reference in fashion studies. Yet, analysis of this philosophical-sociological text rarely compares the different versions of 1895, 1905 and 1911. In order to shed light on Simmel’s approach, this article examines the different essays in the context of Berlin fashion, which the author could observe during its socio-economic and cultural changes. Following comparison of the texts with each other and the texts with their context, Simmel’s view no longer appears as a rigid theory, but rather as a methodological approach to sociological and historical observation.